Impact of Air Pollution on the Ocular Surface and Tear Cytokine Levels: A Multicenter Prospective Cohort Study - Hao, Ran; Zhang, Mingzhou; Zhao, Liming; Liu, Yang; Sun, Min; Dong, Jing; Xu, Yanhui; Wu, Feng; Wei, Jinwen; Xin, Xiangyang; Luo, Zhongping; Lv, Shuxuan; et al. (Frontiers in Medicine, 2022)
Purpose To assess air pollution-induced changes on ocular surface and tear cytokine levels. Methods As a prospective multicenter cohort study, 387 dry eye disease (DED) participants were recruited from five provinces in China and underwent measurements of ocular surface disease index (OSDI), Schirmer’s I test (ST), tear meniscus height (TMH), tear film break-up time (TBUT), corneal fluorescein staining (CFS), meibomian gland (MG) function, and tear cytokines. The associations between ocular surface parameters and exposure to particulate matter (PM), ozone (O3), nitrogen dioxide (NO2), and sulfur dioxide (SO2) for 1 day, 1 week, and 1 month before the examination were analyzed in single- and multi-pollutant models adjusted for confounding factors. Results In the multi-pollutant model, the OSDI score was positively correlated with PM with diameter ≤2.5 μm (PM2.5), O3, and SO2 exposure [PM2.5: β (1 week/month) = 0.229 (95% confidence interval (CI): 0.035–0.424)/0.211 (95% CI: 0.160–0.583); O3: β (1 day/week/month) = 0.403 (95% CI: 0.229–0.523)/0.471 (95% CI: 0.252–0.693)/0.468 (95% CI: 0.215–0.732); SO2: β (1 day/week) = 0.437 (95% CI: 0.193–0.680)/0.470 (95% CI: 0.040–0.901)]. Tear secretion was negatively correlated with O3 and NO2 exposures but positively correlated with PM2.5 levels. Air pollutants were negatively correlated with TBUT and positively related with CFS score. Besides SO2, all other pollutants were associated with aggravated MG dysfunction (MG expression, secretion, and loss) and tear cytokines increasement, such as PM2.5 and interleukin-8 (IL-8) [β (1 day) = 0.016 (95% CI: 0.003–0.029)], PM with diameter ≤10 μm (PM10) and IL-6 [β (1 day) = 0.019 (95% CI: 0.006–0.033)], NO2 and IL-6 [β (1 month) = 0.045 (95% CI: 0.018–0.072)], among others. The effects of air pollutants on DED symptoms/signs, MG functions and tear cytokines peaked within 1 week, 1 month, and 1 day, respectively. Conclusion Increased PM2.5, O3, and SO2 exposures caused ocular discomfort and damage with tear film instability. PM10 exposure led to tear film instability and ocular injury. PM, O3, and NO2 exposures aggravated MG dysfunction and upregulated tear cytokine levels. Therefore, each air pollutant may influence DED via different mechanisms within different time windows.